Partnerships as Entities, Agreements, and Venues to Interact: The Case of the Uganda Aids Commission and the Uganda HIV/AIDS Partnership - Namara, Rose B.; Bergh, Sylvia I. (Uganda Management Institute, 2011)
Partnerships as a framework for development have long been used in the delivery of public policy and programmes. However, the literature suggests that the concept of partnership is often uncritically used and partnerships are understood and practised differently in the delivery of public services. Yet there is little research on the discourse, interests and practices of partnership arrangements and the range of structural factors and agendas underlying these relationships. This article is based on a rapid assessment of the HIV/AIDS Partnership in Uganda as coordinated by the Uganda AIDS Commission (UAC) to explore: (i) how actors (and the UAC in particular) understand the concept of partnership in everyday development delivery and (ii) how actors (and the UAC in particular) practise the concept of partnership. Data drawn from in-depth interviews with UAC management and technical staff as well as key policy documents demonstrates that in the HIV/AIDS sub-sector in Uganda, partnerships are understood and practised as an important methodology of conducting HIV/AIDS interventions. By applying the model developed by Kingsley and Waschak to the empirical data, the article shows that the UAC sees the HIV/AIDS Partnership predominantly as a way of bringing together different entities to make a contribution. Intentionally or not, the HIV/AIDS Partnership serves several purposes, including: improving governance and decision-making processes, streamlining HIV/AIDS resource mobilisation and utilisation, enhancing coordination of the HIV/AIDS response at the decentralised government level, and generally contributing to an effective management of the ever-increasing web of actors in the sector. To a lesser extent, the UAC also conceives of the HIV/AIDS Partnership as a venue of interaction for learning purposes, mainly through the Partnership Forum, and as contractual agreements, especially in the management of the Civil Society Fund where civil society organisations compete for service delivery funding.
Keywords: Partnerships; HIV/AIDS; Health; Uganda